Mulberry Leaf Powder as Protein Alternative for Poultry: A Review - Rukkiya Siddiqui; Meesam Raza; B.C. Mondal; Rashmi Goswami; Sawan Kumar; Muteeb Ullah Rafiqui; Sudhir Kumar; Damini Arya (Archives of Current Research International, 2024)
Poultry production is one of the most important livestock sectors as it provides the cheapest animal protein in the form of eggs and meat for human consumption in the shortest period. Feed cost typically accounts for 60-75% of the total cost of poultry production. However, feed availability is decreasing due to the increasing demands of an expanding human population and significantly increased levels of biofuel production. Therefore, finding economical, cost-effective, and locally available alternatives to conventional feed sources could be one way to reduce poultry feed costs. Mulberry leaves, which have a high nutritional value, can be added to the list of feed alternatives for poultry feeding. Mulberry leaf fodder can be employed successfully in the poultry diet. They are readily digestible (70-90 %) by herbivorous animals as well as monogastric and are found to contain little or no anti-nutritional factor or toxic compounds. It positively influences the growth performance and nutrient utilization in broiler and laying hens. It has been found that mulberry leaves contain a variety of active substances, including polysaccharides, flavonoids, and polyphenols, which can reduce blood glucose and triglycerides, and have the function of antioxidation and regulation of lipid metabolism. The yolk colour has been improved in the eggs of the birds fed with mulberry leaf powder, which can be due to excessive amounts of xanthophylls in the leaves. Mulberry leaves also have an enormous potential to reduce feed cost as they can be used instead of expensive protein sources such as soybean meal and fish meal in poultry diets. Studies conducted with poultry indicated that addition of mulberry leaves are possible up to certain limits in poultry diets without any adverse effect on their performance.